Clinical and genetic characterization of autosomal recessive stickler syndrome caused by novel compound heterozygous mutations in the COL9A3 gene. Issue 3 (11th February 2021) - Markova, Tatiana; Sparber, Peter; Borovikov, Artem; Nagornova, Tatiana; Dadali, Elena
Abstract: Background: Stickler syndrome (STL) is a clinically variable and genetically heterogeneous collagenopathy characterized by ophthalmic, auditory, skeletal, and orofacial abnormalities. STL is mainly inherited in an autosomal dominant pattern with mutations in the COL2A1, COL11A1, and COL11A2 genes. Autosomal recessive forms are rare. However, 19 patients have been reported to date, with STL caused by homozygous or compound heterozygous mutations in genes that encode for the three chains of type IX collagen: COL9A1, COL9A2, and COL9A3 . Methods: Genetic analysis was performed using the next‐generation sequencing of 166 genes associated with skeletal disorders and sequenced on an Ion Torrent S5 system with a minimum coverage of 100X. The two variants in the COL9A3 gene identified in the proband and the parents were confirmed by Sanger sequencing on an ABI3130xl sequencer. Results: We describe a novel case of autosomal recessive Stickler syndrome caused by two undescribed mutations in the COL9A3 gene: c.268C>T (p.Arg90Ter) and c.1729C>T (p.Arg577Ter). The clinical features included severe sensorineural hearing loss, high myopia, vitreoretinal degeneration, and early‐onset arthropathy of the lower limbs. Radiography revealed mild spondyloepiphyseal dysplasia. Conclusion: This case further expands the mutational and phenotypic spectrum of COL9A ‐associated STL with a more severe presentation. Abstract : We describe a novel case of autosomal recessive Stickler syndrome caused by two undescribed loss of function mutations in the COL9A3 gene. Our patients have the more severe phenotype that included severe sensorineural hearing loss, high myopia, vitreoretinal degeneration, mild spondyloepiphyseal dysplasia, and early‐onset arthropathy of the lower limbs.